Association of Post-Operative Infection and MI with Metabolic Syndrome after Coronary Artery Bypass Graft - Ghulam Kibriya, Amna Abbas, Hina Aftab, Muhammad Athif Akram, Yahya Saeed, Omar Iqbal, Azhar Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out association of metabolic syndrome with early outcomes e.g.(post operative infection, acute kidney injury, and MI) after CABG. Study Design: This was a comparative study. Place and Duration: This study was performed from the first of July 2020 to the first of January 2021 at the Cardiac Surgery Department, PIC, Jail Road, Lahore Methodology: This comparative study performed from the first of July 2020 to the first of January 2021 at the Cardiac Surgery Department, PIC, Jail Road, Lahore. The approach of non-probability sampling was applied. After obtaining consent on a consent form, 172 Patients (86 in the exposed group and 86 in the non-exposed group) were included. Results: The average age of the participants in this study was 55.30 ± 8.77 years; there were 130 cases (75.6%) of men and 42 cases (24.4%) of women. There were 56 (65.12%) men and 30 (34.88%) women in the exposed group, compared to 74 (86.05%) men and 12 (13.95%) women in the non-exposed group. Post-operative MI was statistically insignificant in both groups, p-value >0.05, renal failure and postoperative infection were statistically significant. Conclusion: Because many MetS syndrome factors are under our control, it is important to prevent it early especially in cases of CABG, to get better outcomes. Although we noted that renal failure and postoperative infection were statistically high in exposed groups, with a p-value of 0.05, and MI was statistically similar in both groups, with a p-value of >0.05, the outcomes of the current study were quite different and unexpected. Further studies are suggested to be done on a larger scale. Keywords: CABG, Lipid Profile, Diabetes, Obesity, Mortality